Feasibility of reirradiation in the treatment of locally recurrent rectal cancer. Issue 10 (22nd July 2014) - Bosman, S. J.; Holman, F. A.; Nieuwenhuijzen, G. A. P.; Martijn, H.; Creemers, G.‐J.; Rutten, H. J. T.
<x xml:space="preserve">Abstract</x> Background Many patients with locally recurrent rectal cancer receive radiotherapy for the treatment of the primary tumour. It is unclear whether reirradiation is safe and effective when a local recurrence develops. The aim of this study was to evaluate the toxicity and oncological outcome of reirradiation in patients with locally recurrent rectal carcinoma. Methods From March 1994 until December 2013, data on patients with locally recurrent rectal cancer (without distant metastasis) were entered into a database. Patients were reirradiated with a reduced dose of 30 Gy and received an intraoperative electron radiotherapy boost during surgery. Morbidity associated with radiotherapy, postoperative complications and oncological outcome were evaluated. Results Clear margins (R0) were obtained in 75 (55·6 per cent) of the 135 patients who were reirradiated. Forty‐six patients developed serious postoperative complications and the 30‐day mortality rate was 4·6 per cent. Multivariable analysis showed that margin status was the main factor influencing oncological outcome (hazard ratio for overall survival 2·51 for R1 and 3·19 for R2 versus R0 resection; both P < 0·001). There was no significant difference in survival between the reirradiated group and a group of 113 patients who had full‐course irradiation (5‐year overall survival rate 34·1 and 39·1 per cent respectively; P = 0·278). Both reirradiation and full‐course irradiation were associated with better survival than no irradiation in a historical control group of 24 patients (5‐year overall survival rate 23 per cent; P = 0·225 and P = 0·062). Conclusion Reirradiation (with concomitant chemotherapy) has few side‐effects and complements radical resection of recurrent rectal cancer.